Numerical simulation of high pressure burner with partially premixed flame - Lezcano-Benítez, Juan-Camilo; Correa-Restrepo, Daniel; Amell-Arrieta, Andrés-Adolfo; Cadavid-Sierra, Francisco-Javier (CT&F - Ciencia, Tecnología y Futuro, 2011)
In this paper we present the results of a 2D‑axisymmetric parametric study which simulates an atmospheric premixed burner with flame at high pressure, in which methane is burned. A total of 9 simulations are performed with different regulators openings of primary and secondary air. Also, it provides a 3D simulation in which entry conditions are the profiles obtained in a 2D‑axisymmetric simulation, with the intention to note that differences are obtained between 2D and 3D simulation. The simulations are performed using the standard k-ε model for turbulence, P1 model for radiation and the Finite Rate/Eddy Dissipation model with a simplified 2-step reaction mechanism for combustion. We conclude that when the secondary air regulator is closed, combustion is incomplete. Also, the results of 2D‑axisymmetric are a good approximation in regards to 3D results.